Stakeholder Theory in Corporate Sustainability and Integrated Reporting: A Systematic Literature Review - Lisa Maharani; Nasya Paramiya Sari; Zul Azmi (Escalate : Economics and Business Journal, 2026)
This study investigates how Stakeholder Theory explains corporate motivations and practices in sustainability and integrated reporting amid growing pressure for transparent ESG disclosure. The research aims to synthesize conceptual and empirical evidence on the role of stakeholder engagement, governance mechanisms, and compliance with GRI and Integrated Reporting frameworks in shaping reporting quality and corporate legitimacy. A qualitative Systematic Literature Review was conducted using the PRISMA protocol, with Google Scholar as the primary database for 2018–2025 publications. The population comprised 75,600 articles identified with the keywords “Stakeholder Theory,” “Sustainability Reporting,” and “Integrated Reporting,” from which 11 peer-reviewed journal articles were selected through staged identification, screening, and eligibility assessment. The PRISMA flow, inclusion–exclusion criteria, and descriptive tables served as instruments, while thematic synthesis and qualitative quality appraisal were used for data analysis. The results show that Stakeholder Theory is the predominant lens explaining how stakeholder pressure and engagement enhance disclosure transparency, reporting quality, governance discipline, and perceived legitimacy, although findings differ across regulatory and industry contexts. The study concludes that non-financial reporting functions as a strategic accountability instrument, yet methodological heterogeneity and single-database dependence limit generalizability, indicating the need for broader, multi-database, and mixed-method research in future studies